Social Media Usage for Patients and Healthcare Consumers: A Literature Review - Ariana-Anamaria Cordoş; Sorana Daniela Bolboacă; Cristina Drugan (Publications, 2017)
The evolution of Internet from static Web “publishing” to the highly participative, and data-driven, innovations of Web 2.0 has been influencing how people search for health-related information. This review included studies indexed in the PubMed electronic database that focused on social media analysis, examining relationships between participants (patients and healthcare consumers) through social media usage. The obtained results showed that previous research regarding social media’s impact on patients and healthcare consumers aimed at a combination of platforms, but there is a penury of information about niche topics or its usage for retrieving medical information. Nevertheless, social media proved to be to be a promising tool in research mainly for recruitment purposes. The review has outlined that eHealth literacy is an attribute for populations that are female and relatively young and educated. Blogs share personal experiences, YouTube contains unregulated, high- and low-quality information that can mislead individuals, Facebook contains more marketing than health-related information, while Wikipedia is recommended for providing high-quality information. Despite healthcare practitioners’ and healthcare public institutions’ reluctance about the use of social media, this review demonstrates the usefulness of social media for patients and healthcare consumers in retrieving health-related information based on content availability and usage implications, and highlights gaps in knowledge that further research needs to fill.